Plasmodium falciparum Plasmodium helical interspersed subtelomeric proteins contribute to cytoadherence and anchor P. falciparum erythrocyte membrane protein 1 to the host cell cytoskeleton. (26th April 2016) - Oberli, Alexander; Zurbrügg, Laura; Rusch, Sebastian; Brand, Françoise; Butler, Madeleine E.; Day, Jemma L.; Cutts, Erin E.; Lavstsen, Thomas; Vakonakis, Ioannis; Beck, Hans‐Peter
Summary: Adherence of Plasmodium falciparum ‐infected erythrocytes to host endothelium is conferred through the parasite‐derived virulence factor P. falciparum erythrocyte membrane protein 1 (PfEMP1), the major contributor to malaria severity. PfEMP1 located at knob structures on the erythrocyte surface is anchored to the cytoskeleton, and the Plasmodium helical interspersed subtelomeric (PHIST) gene family plays a role in many host cell modifications including binding the intracellular domain of PfEMP1. Here, we show that conditional reduction of the PHIST protein PFE1605w strongly reduces adhesion of infected erythrocytes to the endothelial receptor CD36. Adhesion to other endothelial receptors was less affected or even unaltered by PFE1605w depletion, suggesting that PHIST proteins might be optimized for subsets of PfEMP1 variants. PFE1605w does not play a role in PfEMP1 transport, but it directly interacts with both the intracellular segment of PfEMP1 and with cytoskeletal components. This is the first report of a PHIST protein interacting with key molecules of the cytoadherence complex and the host cytoskeleton, and this functional role seems to play an essential role in the pathology of P. falciparum .